2017
DOI: 10.1007/s10551-017-3747-4
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Us, You Know, There’s a Feeling of Community”: Exploring Notions of Community in a Consumer Co-operative

Abstract: The notion of community infers unity and a source of moral obligations in an organisational ethic between individuals or groups. As such, a community, having a strong sense of collective identity, may foster collective action to promote social change for the betterment of society. This research critically explores notions of community through analysing discursive identity construction practices within a member owned urban consumer cooperative (CC) public house in the UK. A strong sense of community is an often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 74 publications
2
18
0
Order By: Relevance
“…Essentially, these cultural characteristics of a strong form of collectivism also may generate pattern of behaviors (Kolk & Rivera‐Santos, 2018; Zoogah et al, 2015). As consequence, our results inform the literature on knowledge management and intellectual capital, highlighting that the quality of relationships and external support may result from peculiar characteristics of African countries, such as a strong sense of belonging (Lashitew et al, 2020) and a sense of community (Michalopoulos & Papaioannou, 2015; Wells et al, 2019). Further, African countries strongly share a social entrepreneurial orientation (Bacq et al, 2015) and therefore represent a fruitful ground to study the social entrepreneurship phenomenon (Ciambotti et al, 2020; Zahra et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Essentially, these cultural characteristics of a strong form of collectivism also may generate pattern of behaviors (Kolk & Rivera‐Santos, 2018; Zoogah et al, 2015). As consequence, our results inform the literature on knowledge management and intellectual capital, highlighting that the quality of relationships and external support may result from peculiar characteristics of African countries, such as a strong sense of belonging (Lashitew et al, 2020) and a sense of community (Michalopoulos & Papaioannou, 2015; Wells et al, 2019). Further, African countries strongly share a social entrepreneurial orientation (Bacq et al, 2015) and therefore represent a fruitful ground to study the social entrepreneurship phenomenon (Ciambotti et al, 2020; Zahra et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, research in social entrepreneurship demonstrates the relevance of social ties, informal networks, and community engagement for social entrepreneurs. For instance, Wells, Ellis, Slack, and Moufahim (2019) document the importance of engaging the community in cooperatives for the sustainability of the company. This study supports Seelos et al (2011) which revealed the importance of community embeddedness for social entrepreneurs.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…In analysing the data, we followed an iterative method similar to that outlined in Smith-Lacroix et al (2012) and commonly applied to interview-based work (Grossi and Thomasson, 2015; Thomson et al , 2015) during which we reflected on our contextual understanding of the data (Wells et al , 2019). A number of steps were undertaken in this process.…”
Section: Methodsmentioning
confidence: 99%
“…This independence enables the owner to innovate tactically and strategically. Pubs are usually the focal point of British communities and are particular valued as community assets within rural settlements, where they are usually the most popular places for local residents to relax, socialise, drink and eat (Cabras and Reggiano, 2010;Mount and Cabras, 2015;Wells et al, 2019).…”
Section: Pennine Pubsmentioning
confidence: 99%